ADULT ONSET ALEXANDER DISEASE: A DIAGNOSIS TO CONSIDER IN LATE–ONSET SPORADIC SPINOCEREBELLAR ATAXIA. Issue 11 (9th October 2013) - Paramesan, Vahini; MacKinnon, Andrew D; Omer, Salah
Abstract : Alexander disease is a neurodegenerative disease affecting astrocytes, caused by mutations in the gene encoding the glial fibrillary acidic protein (GFAP). The clinical features of this disease, have been described, in children, over the course of sixty years, however, the advent of magnetic resonance imaging (MRI) and molecular genetics have led to an increase in awareness, and allowed the diagnosis of a different clinical and radiological phenotype of an adult–onset form of the disease (AOAD), although it remains under recognised and misdiagnosed. We describe the cases of 2 male patients with AOAD, with characteristic MRI appearances, and novel mutations in the GFAP gene. The first patient presented with falls and cognitive impairment, and exhibited cerebellar signs. He later developed bulbar symptoms with considerable difficulty swallowing. The second patient presented with falls and changes in behaviour, with evidence of pyramidal and cerebellar signs on examination. Both patients demonstrated significant frontal executive dysfunction on neuropsychometric tests, a feature which has not been described previously. Our literature review identified two other cases, of AOAD, with behavioural changes, which were thought to be independent of the disease process. We suggest that cognitive and behavioural changes are in fact manifestations of AOAD. In addition, we report two novel mutations of the GFAP gene.